2011
DOI: 10.1002/app.34744
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Luffa cylindrica fibers and the effect of water aging on the mechanical properties of its composite with polyester

Abstract: Luffa cylindrica of Turkey's Aegean Region was evaluated in terms of fiber characterization and the mechanical properties of its composite with polyester. Characterization of Luffa cylindrica was carried out by Fourier transform infrared spectrophotometer, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy, and thermogravimetric analysis. Cellulose, hemicellulose, and lignin contents of Luffa cylindirica were also determined. Deconvolutions of XPS data enable determining the distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 33 publications
0
39
0
3
Order By: Relevance
“…This treatment removes a certain amount of lignin, wax, and hemicelluloses of the fiber cell wall, depolymerizes cellulose, and exposes the short-length cellulose fibril. The ionization of hydroxyl groups of fibers into alkoxide increases the fiber strength and stiffness and hence, increases mechanical properties (Demir et al 2006;Seki et al 2011). The weight changes of the fibers after alkali treatments were determined gravimetrically and a loss of weight was observed near 2%.…”
Section: Chemical Treatment Of Fiber Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…This treatment removes a certain amount of lignin, wax, and hemicelluloses of the fiber cell wall, depolymerizes cellulose, and exposes the short-length cellulose fibril. The ionization of hydroxyl groups of fibers into alkoxide increases the fiber strength and stiffness and hence, increases mechanical properties (Demir et al 2006;Seki et al 2011). The weight changes of the fibers after alkali treatments were determined gravimetrically and a loss of weight was observed near 2%.…”
Section: Chemical Treatment Of Fiber Surfacementioning
confidence: 99%
“…1. Parts of the plant are used to create bath or kitchen sponges, a natural jaundice remedy (juice), home insulation, furniture, and various other products (Demir et al 2006;Seki et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In these investigations, the reported mechanical properties such as tensile strength, flexural strength, Young's modulus, and tangent modulus of untreated SGF reinforced composites were less than those obtained by treated [17]. These authors have shown that when the modified fiber is added to polymer matrix, the composites exhibit a significant increase in mechanical properties as compared to the untreated ones.…”
Section: Introductionmentioning
confidence: 98%
“…Luffa cylindrica fibers (also called loofah or sponge gourd) are a noteworthy alternative to mineral fibers. Their low cost and low density are the major benefits for their use in composites (Boynard and d'Almeida 2000;Chen and Lin 2005;Paglicawan et al 2005;Zampieri et al 2006;Demir et al 2008;Kocak 2008;Seki et al 2012;Shen et al 2013). However, the characteristics (especially the dynamic or modal properties) of these new materials should be investigated in order to use them effectively in practical applications such as vibration attenuation of machines and sound isolation of conference rooms.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some studies on the morphology, thermodynamics, energy absorption, and elastic properties of luffa materials (Boynard and D'Almeida 2000;Chen and Lin 2005;Paglicawan et al 2005;Zampieri et al 2006;Demir et al 2008;Kocak 2008;Ghali et al 2009;Satyanarayana et al 2009;Seki et al 2012;Shen et al 2012Shen et al , 2013Kocak et al 2013;Genc 2015;Genc and Koruk 2016a). Koruk and Genc (2015) showed that the sound absorption of luffa composites is considerably high.…”
Section: Introductionmentioning
confidence: 99%